Reevaluation of the Palladium/Carbon-Catalyzed Decarbonylation of Aliphatic Aldehydes - Ajdačić, Vladimir; Nikolić, Andrea; Kerner, Michael; Wipf, Peter; Opsenica, Igor M. (Synlett, 2018)
An improved method for the decarbonylation of aliphatic aldehydes by using a commercially available Pd/C catalyst is described. The reaction conditions are suitable for linear, cyclic, or sterically demanding substrates, as they afford the corresponding alkanes in yields of up to 99%. In addition, this Pd/C-catalyzed method exhibits good functional-group tolerance. A comparison of previously reported methods with the present one showed that the reaction conditions play a crucial role in the outcome of the reaction. The method can also be applied in a two-step reaction sequence for the synthesis of industrially important compounds.
Keywords: decarbonylation; aldehydes; palladium catalysis; adamantine; alkylated aromatic compounds; natural products